Pengaruh MInat dan Motivasi Belajar Terhadap Kemampuan Belajar Al-Qur'an Hadist Siswa Kelas VII di MTsN 1 Watampone - Abidin, A. Asriani (Institut Agama Islam Negeri (IAIN) Bone, 2018)
This paper examines the influence of the interest and motivation of learning towards the learning capabilities of the qur'an the Hadith grade VII MTs N country 1 Watampone. The results showed that interest is a cornerstone of most convincing for the sake of the success of a learning process. If a siswamemiliki sense of wanting to learn, he would quickly be able to understand and remember it. Learning would be an ordeal and will not benefit if not accompanied by nature open to lesson materials. Successful teachers foster student learning willingness means has done the most that can be done in the interest of learning to their students. Because interest is not something that exists, but rather something that can be learned. Motivation and learning is a combination of two words, i.e. words of motivation and learning. Motivation means impulse arising on a person to perform an objective, and the boost could come from outside or from within himself. The learning interest and motivation of learning is an important factor that should be owned by the students in learning. Interest in learning the soul grows in grade VII MTsN 1 Watampone is definitively affect the process and how to learn, when their students learning materials that are studied are not in accordance with the interest, the student will not learn by best foot forward because there is no power pull for him.